Dendritic Systems Based on Dinuclear Ruthenium or Rhodium Units Generating Peripheral Catalytic Sites - Chérioux, Frédéric; Thomas, Christophe M.; Therrien, Bruno; Süss-Fink, Georg (My University, 2002)
Nous avons synthétisé et caractérisé les nouveaux cations dendritiques 1-4 contenant les unités Ru2S3 ou Rh2S3. L'analyse de la structure aux rayons X de 2-Cl montre un coeur Rh2S3à géométrie bipyramide trigonale. La réaction des groupements OH périphériques avec l'acide 2-diphénylphosphinobenzoïque permet la formation des cations dendritiques 5-8 fonctionnalisés par des phosphines. Le cation 5 qui contient deux atomes de ruthénium au centre et trois fonctions PPh2 à la périphérie peut servir de ligand avec le rhodium(I) et permettre d'augmenter significativement l'activité catalytique du précurseur [{Rh(CO)2Cl}2] pour la carbonylation du méthanol., A series of dendritic cations 1-4 containing Ru2S3 or Rh2S3 units, either in the core or in the dendrons, has been synthesized and characterized. The X-ray crystal structure analysis of 2-Cl shows a trigonal bipyramidal Rh2S3 core with propeller-like para-hydroxyphenyl substituents at the sulfur atoms. Reaction of the peripheral OH groups with diphenylphosphino benzoic acid results in the formation of phosphine-functionalized dendritic cations 5-8. The ruthenium-containing cation 5, with three PPh2 functions at the periphery, acts as ligand for rhodium(I) and enhances significantly the catalytic activity of [{Rh(CO)2Cl}2] for the carbonylation of methanol.
Keywords: catalysts; dendrimers; rhodium; ruthenium